TurboID Identification of Evolutionarily Divergent Components of the Nuclear Pore Complex in the Malaria Model Plasmodium berghei - Sushma V. Ambekar; Josh R. Beck; Gunnar R. Mair (mBio, 2022)
ABSTRACT Twenty years since the publication of the Plasmodium falciparum and P. berghei genomes one-third of their protein-coding genes still lack functional annotation. In the absence of sequence and structural homology, protein-protein interactions can facilitate functional prediction of such orphan genes by mapping protein complexes in their natural cellular environment. The Plasmodium nuclear pore complex (NPC) is a case in point: it remains poorly defined; its constituents lack conservation with the 30+ proteins described in the NPC of many opisthokonts, a clade of eukaryotes that includes fungi and animals, but not Plasmodium. Here, we developed a labeling methodology based on TurboID fusion proteins, which allows visualization of the P. berghei NPC and facilitates the identification of its components. Following affinity purification and mass spectrometry, we identified 4 known nucleoporins (Nups) (138, 205, 221, and the bait 313), and verify interaction with the putative phenylalanine-glycine (FG) Nup637; we assigned 5 proteins lacking annotation (and therefore meaningful homology with proteins outside the genus) to the NPC, which is confirmed by green fluorescent protein (GFP) tagging. Based on gene deletion attempts, all new Nups — Nup176, 269, 335, 390, and 434 — are essential to parasite survival. They lack primary sequence homology with proteins outside the Plasmodium genus; albeit 2 incorporate short domains with structural homology to human Nup155 and yeast Nup157, and the condensin SMC (Structural Maintenance Of Chromosomes 4). The protocols developed here showcase the power of proximity labeling for elucidating protein complex composition and annotation of taxonomically restricted genes in Plasmodium. It opens the door to exploring the function of the Plasmodium NPC and understanding its evolutionary position. IMPORTANCE The nuclear pore complex (NPC) is a platform for constant evolution and has been used to study the evolutionary patterns of early-branching eukaryotes. The Plasmodium NPC is poorly defined due to its evolutionary divergent nature making it impossible to characterize it via homology searches. Although 2 decades have passed since the publication of the Plasmodium genome, 30% of the genes still lack functional annotation. Our study demonstrates the ability of proximity labeling using TurboID to assign function to orphan proteins in the malaria parasite. We have identified a total of 10 Nups that will allow further study of NPC dynamics, structural elements, involvement in nucleocytoplasmic transport, and unique non-transport functions of nucleoporins that provide adaptability to this malaria parasite.